Peran Lembaga Pemasyarakatan Terhadap Residivis Dalam Upaya Reintegrasi Sosial - Maghfiroh, Laily; Lewoleba, Kayus Kayowuan (Media Hukum Indonesia (MHI), 2024)
Residivis refers to the recidivism of criminal acts after serving a prison sentence as determined by the court. The Correctional Institution was established to provide guidance to inmates so that they can return to society with a better character. There are various factors hindering the effective and efficient functioning of the Correctional Institution. Therefore, this study was conducted using a normative method and a conceptual approach, as well as legal regulations. The results of this study show that the Correctional Institution has a rehabilitation program aimed at social reintegration, thus preparing residivis with various training programs to return to society. However, factors such as overcapacity, untrained staff, inadequate facilities, social stigma, and cultural factors hinder the effectiveness of these programs.